(untitled) (Journal of Medical & Health Sciences Review, 2025)
The importance of aquaculture as a sustainable protein source highlights the need to address challenges like disease outbreaks and poor fish performance. Global difficulties confronting aquaculture include food quality, disease control, water quality and environmental factors. This study aims to evaluate the effectiveness of Lactobacillus-derived probiotic supplements in improving the well-being and illness tolerance of common carp towards Aeromonas hydrophila an infectious microbe that causes considerable losses in aquaculture. Experimental groups of fish were provided with a meal enriched with Lactobacillus-based probiotics, whereas control groups were given a standard diet. After encountering A. hydrophila, the functional as well as structural health of essential organs heart, kidney, gut and gills was determined using histopathological and biochemical investigations. Results demonstrated that probiotic-treated fish displayed less tissue damage, enhanced immunological responses and elevated survival rates relative to non-supplemented controls. The probiotic administration significantly alleviated the detrimental effects of bacterial illness safeguarding the functioning of organs and general fish health. The findings indicate the possibility of Lactobacillus-derived beneficial bacteria as an organic sustainable substitute for antibiotics in disease prevention within aquaculture.